Kepemimpinan Pendidikan Kepala Sekolah dalam Perspektif Al-Qur’an - Zulkhairi, Zulkhairi (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2021)
The research discusses the theory of spiritual leadership and Islamic teachings, and transposes the theoretical components of the spiritual leadership model into an Islamic leadership model that is more suitable for Islamic educational institutions. The research tries to find the concept of leadership in the perspective of the Qur'an. The research method is qualitative type. The technique used is literature study. Data were collected through relevant studies. The results of the study show that leadership in Islam is the term caliph, Imam, and Ulil-Amri; the concepts of caliph, imam, and ulil-Amri are very relevant to leadership in organizations; Surah Al Maidah verse 2 contains various lessons that are important to be absorbed and practiced by every Muslim, especially leaders in society, educational institutions. The context of leadership in society and educational institutions is to increase self-awareness, emotional and social interaction, communication, and daily interactions in the work environment, business and social activities of the community.